Analysis of problems induced by imprecise dating of measurements in oil and gas production. Issue 8 (2015) - Petit, Nicolas
Abstract: In this paper we discuss the negative impact on monitoring algorithms of working with imprecisely dated data. Two examples from the world of the oil & gas industry are presented and serve to illustrate that this problem can be of practical importance. First analytical results show that when signals with significant time variations are monitored, the impact of dating of measurements can be as troublesome (or even worse) than measurement noises.